Post-Colonial English Drama
X, 275 p.
Keywords: Post-Colonial English Drama is the first critical survey of contemporary Commonwealth drama. Besides essays on such individual dramatists as Wole Soyinka, Derek Walcott, David Williamson, Louis Nowra, Athol Fugard, George Walker, Sharon Pollock and Judith Thompson there are surveys of the dramatic literature and developments in the theatre in Australia, Canada, India, New Zealand, South Africa, Papua New Guinea, Ghana, Nigeria, Jamaica and Trinidad. Canadian woman dramatists and the new radical South African theatre are also among the topics.